Analisis Karakteristik Aspal Berdasarkan Batuan Reservoir Kabupaten Buton Provinsi Sulawesi Tenggara: Analysis of Asphalt Characteristics Based on Reservoir Rocks in Buton Regency, Southeast Sulawesi Province - Sukardin, Sukardin; Widodo, Sri; Nurliah Jafar (Journal of Engineering Science and Technology Applications, 2023)
Factors influencing the content of asphalt is the process of formation, moisture content and the type of reservoir rocks, then to do the research on the characteristics of asphalt based on reservoirnya rocks. The purpose of this research is to know the physical nature of Asphalt Buton Rock based on reservoirnya. The method used is the sokhlet method. The data used is data of rocks reservoir site I and II, the physical properties of the data of the asphalt. Of research results obtained at the location I have rocks limestone reservoir with poor porosity features have higher levels of bitumen (23-47%), the asphalt is more dense and hard, CaCO3 content was higher (86,66%) whereas in a location that has a reservoir rock II sandstones with physical characteristics of good porosity have lower levels of bitumen (20-40%), the asphalt is relatively more malleable, a higher SiO2 content (17,06). From the results it can be concluded that the physical nature of asphalt location I have poor porosity and physical properties II location has good porosity, on the location of research levels obtained 20-47%.